Neutrino masses and TeV scale resonant leptogenesis from supersymmetry breaking - West, S (2006)
We review a class of supersymmetric models in which the light neutrino masses result from higher-dimensional supersymmetry-breaking terms in the MSSM super- and Kähler-potentials. The mechanism used in these models is closely related to the Giudice-Masiero mechanism for the MSSM μ parameter and leads to TeV-scale right-handed neutrino and sneutrino states. In these models, the dominant contribution to the light neutrino (Majorana) mass matrix is a one-loop term with a sub-dominant tree-level "seesaw" contribution. It is also shown that it is possible to construct a natural model of TeV-scale leptogenesis via the resonant behavior of the one-loop self-energy contribution to the right-handed neutrino (N i) decay. This model addresses the primary problems of previous phenomenological studies of low-energy leptogenesis: a rational for TeV-scale right-handed neutrinos with small Yukawa couplings; the origin of the tiny, but non-zero mass splitting required between at least two N i masses; and the necessary non-trivial breaking of flavor symmetries in the right-handed neutrino sector. © World Scientific Publishing Company.